2015
DOI: 10.1111/ppc.12141
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Assessment of the Barkin Index of Maternal Functioning in a Medically Underserved Obstetric Population

Abstract: The BIMF has broad appeal due to its comprehensibility, patient-centered assessment style, and psychometric profile. Method of questionnaire administration and characteristics of the study and/or patient population should routinely be considered when implementing any type of self-reported health screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
3
20
1
2
Order By: Relevance
“…Another attractive feature of the BIMF is that it was designed to be applicable in both research and clinical settings and takes only 5-10 min to complete [14]. In a separate language assessment, investigators found that the BIMF's 20 items were comprehensible and clearly worded [33]. In this study, Cronbach's alpha coefficient was 0.88 (indicating good internal consistency) and the Intra Correlation Coefficient (ICC) was equal to 0.85 [35].…”
Section: Maternal Functioningmentioning
confidence: 70%
See 1 more Smart Citation
“…Another attractive feature of the BIMF is that it was designed to be applicable in both research and clinical settings and takes only 5-10 min to complete [14]. In a separate language assessment, investigators found that the BIMF's 20 items were comprehensible and clearly worded [33]. In this study, Cronbach's alpha coefficient was 0.88 (indicating good internal consistency) and the Intra Correlation Coefficient (ICC) was equal to 0.85 [35].…”
Section: Maternal Functioningmentioning
confidence: 70%
“…If interested, eligible, and prepared to participate in regular and continuous sessions, a written consent form was completed by the mothers. They also completed the BIMF [33] and EPDS [31] questionnaires. If they received a score of less than 13 on the EPDS, and a score below 80 on the BIMF, they were included in the study at which point other questionnaires such as the sociodemographic and obstetrics characteristics questionnaire were also completed.…”
Section: Recruitmentmentioning
confidence: 99%
“…Alternatively, in a similar qualitative study of adolescent mothers, the majority of who were single and attending high school, complaints were counterbalanced with positive commentary. 35 Additional qualitative work by Barkin et al 21 was focused on a low-income obstetric population in an area designed as medically underserved. The majority of the participants were on Medicaid (95.8%), and 70.8% reported a total household income of $20,000 or less.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that less affluent women with fewer years of life experience are also less critical in their appraisal of their life circumstances. Barkin et al 21 also note that several women were concerned with the possibility of negative survey responses triggering the involvement of the Division of Family and Children Services, which might have also artificially inflated the BIMF total score. Depression status was not evaluated in this study and it is likely that the group was a mixture of women who would have screened positive (if screened) and women who would not qualify as depressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation